1997
DOI: 10.1017/s0022029997002380
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties at small (dynamic) and large (yield) deformations of acid gels made from heated milk

Abstract: The effect of a range of milk heat treatments on the rheological properties, at small and large deformations, of acid skim milk gels was investigated. Gels were made from reconstituted skim milk heated at 75, 80, 85 and 90°C for 15 or 30 min by acidification with glucono-δ-lactone at 30°C. Gels were also made from skim milk powder (SMP) samples that had been given a range of preheat treatments during powder manufacture. Heating milks at temperatures [ges ]80°C for 15 min increased the storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
228
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(271 citation statements)
references
References 0 publications
25
228
2
1
Order By: Relevance
“…Values of the minimum in tan d appeared rather constant at 0.33 (d = 18.3°) at both temperatures, while the "maximum in tan d" appeared higher at 42°C than at 30°C. These results have been previously reported on heat-treated milk acidified by GDL [22,25,26] and with lactic bacteria [2,27,36,40].…”
Section: Rheological Characterisationsupporting
confidence: 75%
See 2 more Smart Citations
“…Values of the minimum in tan d appeared rather constant at 0.33 (d = 18.3°) at both temperatures, while the "maximum in tan d" appeared higher at 42°C than at 30°C. These results have been previously reported on heat-treated milk acidified by GDL [22,25,26] and with lactic bacteria [2,27,36,40].…”
Section: Rheological Characterisationsupporting
confidence: 75%
“…With heat treatment, tan d first decreases then increases to a local maximum value and finally decreases. According to Lucey et al [25], this behaviour of tan d was observed for a heat treatment at 85°C for 30 min. A great increase in the final value of G' was observed for a heat treatment ³ 80°C for 30 min, at more than 70% denaturation of whey proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denatured whey proteins could act as bridging material by interacting with the whey proteins which are associated with the micelles, which would increase the number and strength of bonds between protein particles. The concentration of potential gelling protein would also be increased due to active participation of denatured whey protein in the gel structure [22]. While denatured whey proteins are known to affect the formation of acid milk gels [22], the mechanism by which they affect the rheological properties is not adequately explained.…”
Section: Introductionmentioning
confidence: 99%
“…In the milk gel, the clusters fuse to roughly homogeneous strands and cannot be (well) distinguished anymore (van Vliet et al 2004). According to the rheological properties, fermented milks can be regarded as weak gel networks (Lucey et al 1997a;van Vliet et al 1991). By stirring, this gel is broken down into more or less stable microgel particles suspended in the whey that conserve the properties of the initial gel (Renan et al 2009) and that have sizes ranging from 1 to 100 μm( C i r o ne ta l .2010; Weidendorfer and Hinrichs 2010).…”
Section: Introductionmentioning
confidence: 99%